ICTV Virus Taxonomy Profile: Filoviridae - Kuhn, Jens H; Amarasinghe, Gaya K; Basler, Christopher F; Bavari, Sina; Bukreyev, Alexander; Chandran, Kartik; Crozier, Ian; Dolnik, Olga; Dye, John M; Formenty, Pierre B H; Griffiths, Anthony; Hewson, Roger; et al. (Journal of general virology, 2019)
Members of the family Filoviridae produce variously shaped, often filamentous, enveloped virions containing linear non-segmented, negative-sense RNA genomes of 15-19 kb. Several filoviruses (e.g., Ebola virus) are pathogenic for humans and are highly virulent. Several filoviruses infect bats (e.g., Marburg virus), whereas the hosts of most other filoviruses are unknown. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on Filoviridae, which is available at www.ictv.global/report/filoviridae.